2012
DOI: 10.1007/s10878-012-9555-y
|View full text |Cite
|
Sign up to set email alerts
|

The cost of selfishness for maximizing the minimum load on uniformly related machines

Abstract: Consider the following scheduling game. A set of jobs, each controlled by a selfish agent, are to be assigned to m uniformly related machines. The cost of a job is defined as the total load of the machine that its job is assigned to. A job is interested in minimizing its cost, while the social objective is maximizing the minimum load (the value of the cover) over the machines. This goal is different from the regular makespan minimization goal, which was extensively studied in a game theoretic context.We study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Similarly to the results of [11], one can argue that for any number of uniformly related machines these measures are unbounded.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…Similarly to the results of [11], one can argue that for any number of uniformly related machines these measures are unbounded.…”
Section: Introductionmentioning
confidence: 54%
“…This is very different from the results in the situation of the makespan minimization social goal, where the poa is finite [5,15]. A study of the cases where the speed ratio is no larger than 2 can be found in [11,20,30].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Chen et al [4] improve the results for the case with identical machines, where the PoS is exactly 1 and the overall PoA is exactly 1.7 for the case with m identical machines. Epstein et al [9] analyze the PoA and PoS for a special case of m uniform machines. Epstein et al [8] and Tan et al [19] completely solve the problem of measuring the inefficiency of equilibria on two uniform machines (see Fig.…”
Section: Introductionmentioning
confidence: 99%